2016
DOI: 10.1038/srep30721
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with an orally bioavailable prodrug of 17β-estradiol alleviates hot flushes without hormonal effects in the periphery

Abstract: Estrogen deprivation has a profound effect on the female brain. One of the most obvious examples of this condition is hot flushes. Although estrogens relieve these typical climacteric symptoms, many women do not want to take them owing to unwanted side-effects impacting, for example, the uterus, breast and blood. Therefore, there is a need for developing safer estrogen therapies. We show here that treatment with 10β,17β-dihydroxyestra-1,4-dien-3-one (DHED), a novel brain-targeting bioprecursor prodrug of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 39 publications
1
31
1
Order By: Relevance
“…In this study, we characterized how estrogen signaling ameliorated cognitive function of AD mice. We found that DHED which is a brain-selective prodrug of 17β-estradiol and produces the hormone only in the brain could improve the memory deficits in Tg2576 transgenic AD model and could decrease Aβ and phosphorylated tau protein levels in the brain of ovariectomized female AD mice (Merchenthaler et al 2016;Prokai et al 2015). Besides, DHED could also enhance superoxide dismutase (SOD) in the hippocampus, while decrease malondialdehyde (MDA).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we characterized how estrogen signaling ameliorated cognitive function of AD mice. We found that DHED which is a brain-selective prodrug of 17β-estradiol and produces the hormone only in the brain could improve the memory deficits in Tg2576 transgenic AD model and could decrease Aβ and phosphorylated tau protein levels in the brain of ovariectomized female AD mice (Merchenthaler et al 2016;Prokai et al 2015). Besides, DHED could also enhance superoxide dismutase (SOD) in the hippocampus, while decrease malondialdehyde (MDA).…”
Section: Introductionmentioning
confidence: 99%
“…Prokai et al found that • OH radical scavenging by estrone yields a p ‐quinol A‐ring‐containing intermediate that subsequently undergoes a NADP‐dependent enzymatic reduction back to estrone, without contributing to oxidative stress on its own but becoming able to scavenge further radicals . In vivo administration of the analogous p ‐quinol derivative of estradiol (DHED) demonstrated no estrogenic activity, and it was rapidly taken up into the brain where it initiated the above‐mentioned redox cycle; therefore it acted as a targeted neuroprotective agent without any apparent systemic side‐effects . On one hand, this provides an attractive strategy to deliver estrogens to the brain through their pro‐drugs.…”
Section: Biological Significance Of Rons Scavenging‐related Antioxidamentioning
confidence: 99%
“…[144][145][146] In vivo administration of the analogous p-quinol derivative of estradiol (DHED) demonstrated no estrogenic activity, and it was rapidly taken up into the brain where it initiated the above-mentioned redox cycle; therefore it acted as a targeted neuroprotective agent without any apparent systemic side-effects. [147][148][149][150] On one hand, this provides an attractive strategy to deliver estrogens to the brain through their pro-drugs. On the other hand, it also represents a good example for a phenolic antioxidant (estradiol or estrone) to be transformed to a metabolite (eg DHED) on a free radical scavenging-related manner.…”
Section: Biological Significance Of Rons Scavenging-related Antioximentioning
confidence: 99%
“…E2 is now also considered as one of the neurosteroids, as its regioselective local formation in the brain has been established [5][6][7][8]. Indeed, with today's modern analytical instrumentations and using validated bioassays that are devoid of the limitations of immunoassays [9], brain E2 level even in ovariectomized animals (i.e., in animals without gonadal E2 source) can be measured [10,11]. It has been hypothesized that this de novo central formation of E2 due to the lack of gonadal E2 sources, for example, as in case of ovariectomy, is essentially a compensatory mechanism to protect the estrogen-deprived brain that cannot receive the hormone from the circulation any more, although plasma estrogen levels do not directly correlate with that of brain [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Among estrogens and estrogenic compounds, E2 also is the best-known estrogen to be used as a powerful neuroprotective agent in various in vitro and preclinical animal models of neurodegeneration impacting the central nervous system (CNS) [16][17][18][19][20]. It is important to emphasize, though, that E2 has a large array of other beneficial effects in the CNS, including regulating body temperature, enhancing cognition and memory and ameliorating neuropsychiatric conditions in both females and males [7,11,[21][22][23]. While the brain is undoubtedly the most frequently studied part of the CNS in the context of neuroprotection [24][25][26], the utility of E2 in protecting the eye (retina and optic nerve) [27][28][29] and spinal cord [30][31][32] have also been explored with promising outcomes.…”
Section: Introductionmentioning
confidence: 99%